Challenges and opportunities in obesity: the role of adipocytes during tissue fibrosis - Zhang, Qian; Lu, Chongxuan; Lu, Feng; Liao, Yunjun; Cai, Junrong; Gao, Jianhua (Frontiers in Endocrinology, 2024)
Obesity is a chronic disease that affects the energy balance of the whole body. In addition to increasing fat mass, tissue fibrosis occurred in white adipose tissue in obese condition. Fibrosis is the over-activation of fibroblasts leading to excessive accumulation of extracellular matrix, which could be caused by various factors, including the status of adipocytes. The morphology of adipocytes responds rapidly and dynamically to nutrient fluctuations. Adaptive hypertrophy of normal adipocytes protects peripheral organs from damage from lipotoxicity. However, the biological behavior of hypertrophic adipocytes in chronic obesity is abnormally altered. Adipocytes lead to fibrotic remodeling of the extracellular matrix by inducing unresolved chronic inflammation, persistent hypoxia, and increasing myofibroblast numbers. Moreover, adipocyte-induced fibrosis not only restricts the flexible expansion and contraction of adipose tissue but also initiates the development of various diseases through cellular autonomic and paracrine effects. Regarding anti-fibrotic therapy, dysregulated intracellular signaling and epigenetic changes represent potential candidate targets. Thus, modulation of adipocytes may provide potential therapeutic avenues for reversing pathological fibrosis in adipose tissue and achieving the anti-obesity purpose.